Diseminasi Pemanfaatan Limbah Pelepah Kelapa Sawit dan Kotoran Sapi menjadi Briket Arang sebagai Bahan Bakar Alternatif di Kampung Majemus Distrik Masni Kabupaten Manokwari - Purwaningsih, Purwaningsih; Saragih, Evi Warintan; Santoso, Budi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The problem faced by our society today is the accumulation of cow feces and palm fronds which are solid biomass waste produced throughout the year by oil palm plantations and livestock businesses. One of the utilization and processing of these two biomass wastes is to make charcoal briquettes as an alternative fuel. Charcoal briquettes have advantages because they have high economic value compared to wood charcoal, higher calorific value, odorless, attractive shape and durable. This dissemination activity is in addition to empowering the community in the application of appropriate waste treatment technology innovations, as well as providing an alternative for developing creative economic potential for the people of Majemus Village, Masni District, Manokwari Regency. The method of implementing this activity is participatory counseling, practice or training and mentoring, so that the product can be continuously produced and ready to be marketed. The manufacture of charcoal briquettes starts from the stages of drying the main raw materials, composing of raw materials, grinding, mixing materials with adhesives, printing briquettes, drying briquettes again, quality testing, and packaging. The final results of the activities carried out showed that (1) they succeeded in disseminating effective and simple innovations in livestock and plantation waste treatment technology and applied in the field, (2) training participants or members of partner groups were involved and played an active role in all activities ranging from counseling to training on practice and training, (3) charcoal briquettes produced SNI standard that will renewable energy source for everyday necessities.